Análisis de los Estados Financieros del comercial CREDI-LOJA de la ciudad de Loja, período 2015 – 2016 - Flores Castillo, Ghina Magdalena (2018)
The thesis work entitled "ANALYSIS OF THE FINANCIAL STATEMENTS OF THE COMMERCIAL CREDI-LOJA OF THE CITY OF LOJA, PERIOD 2015-2016", was carried out with the purpose of determining the situation in which the use of the financial analysis tool is found, information that allows risks and opportunities that contribute to its improvement and efficiency. For the development of the present the second general objective was raised: Analyze and interpret the financial statements of the CREDI-LOJA company of the city of Loja during the period 2015-2016; In order to know the economic-financial situation, in order to perform the financial analysis of the business, the specific objectives were fulfilled, proceeding to the application of the vertical and horizontal analysis, to determine the financial structure of the 2015-2016 commercial period and determine the causes that originate the increases and decreases in the different items that make up the financial statements. Financial indicators were applied to measure administrative and financial management, determining the liquidity, activity, indebtedness and profitability of the company, through which it was known that the commercial has liquidity to cover its short-term obligations, the turnover of accounts receivable and inventories in the periods analyzed is less than 30 days, so they must maintain collection strategies since they are the key to cash income and also implement promotions that contribute to the rotation of the inventories, additionally the company has a low level of indebtedness with suppliers and no type of indebtedness with financial institutions, which shows that the commercial operates with its own capital. With the DuPont system it was determined that the market profitability, a slightly larger period of time, for what is shown as a resource management. The equilibrium point represents the level of sales that the commercial requires that the total costs, demonstrating that it does not meet this value the company will incur profits and if the opposite happens the commercial. Finally, a report was prepared for the owner of the financial analysis of the business in order to publicize the efficiency and effectiveness with which he manages his resources.